2020
DOI: 10.1021/acs.jpcb.0c00657
|View full text |Cite
|
Sign up to set email alerts
|

Water-Mediated Electronic Structure of Oligopeptides Probed by Their UV Circular Dichroism, Absorption Spectra, and Time-Dependent DFT Calculations

Abstract: We investigate the UV absorption spectra of a series of cationic GxG (where x denotes a guest residue) peptides in aqueous solution and find that the spectra of a subset of peptides with x = A, L, I, K, N, and R (and, to a lesser extent, peptides with x = D and V) vary as a function of temperature. To explore whether or not this observation reflects conformational dependencies, we carry out time-dependent density functional calculations for the polyproline II (pPII) and β-strand conformations of a limited set … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…41 Finally, the calculations of the UV-electronic circular dichroism (UV-ECD) and UV-Photoabsorption spectra have been performed at the Time-Dependent DFT (TDDFT) level analyzing the lowest 70 and 100 excited-states for GAG + and (GVGVP) 2 , respectively. In order to allow an easy comparison with the experimental data, [28][29][30][31] the calculated spectra have been reported in terms of ε (photoabsorption) and Δε (ECD). The individual UV-ECD spectra relative to the most relevant conformations in presence of the explicit solvent are reported in Figures S3-S8.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…41 Finally, the calculations of the UV-electronic circular dichroism (UV-ECD) and UV-Photoabsorption spectra have been performed at the Time-Dependent DFT (TDDFT) level analyzing the lowest 70 and 100 excited-states for GAG + and (GVGVP) 2 , respectively. In order to allow an easy comparison with the experimental data, [28][29][30][31] the calculated spectra have been reported in terms of ε (photoabsorption) and Δε (ECD). The individual UV-ECD spectra relative to the most relevant conformations in presence of the explicit solvent are reported in Figures S3-S8.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…The position of this amide band is significantly red shifted in comparison with the average positions observed in amides, [71] including peptidic and pseudopeptidic structures. [36,72,73] This must be attributed to the influence of the solvent and the long aliphatic tails, as red shifts are usually reported for n-* transitions of amides when changing the solvent from polar to apolar. [71] The second band, less intense and with the fine structure partly observed, appears in the 255-280 nm region and is associated to the substituted benzene ring of the spacer.…”
Section: Uv-vis and CD Studiesmentioning
confidence: 84%
“…We chose these three functionals because hydrogen bonding interactions and excited state energies are found very close to the gold standard CC2 or CCSD(T) methods. 34,35 Very recently, Kumar et al reported that wB97XD/cc-pVTZ functional is essential for accurate prediction of chargetransfer excitations and hydrogen bonding interactions. 35 The low-lying 10 excited singlet states were calculated at wB97XD-optimized S 0 geometries for all the clusters and the excited state dipole moments were calculated at the same level of theory.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Besides, electronic structure calculations were carried out by time‐dependent density functional theory (TD‐DFT) methods employing M06‐2X, w B97XD, and CAM‐B3LYP functionals with cc‐pVTZ basis set. We chose these three functionals because hydrogen bonding interactions and excited state energies are found very close to the gold standard CC2 or CCSD(T) methods 34,35 . Very recently, Kumar et al reported that w B97XD/cc‐pVTZ functional is essential for accurate prediction of charge‐transfer excitations and hydrogen bonding interactions 35 .…”
Section: Computational Detailsmentioning
confidence: 99%